Physico-Chemical Parameters of Krishna River Water Especially at Jawahar Nettempadu Project - Rajasekhar Reddy, V. (International Journal of Psychosocial Rehabilitation, 2021)
The physico-chemical parameters of Krishna river water was studied in the month of January 2020. Seven samples were collected from different locations. The parameters like pH, EC, TDS, TS, BOD and DO etc. were determined in Water quality Monitoring laboratory, Wanaparthy,JogulambaGadwaldisrict. The results obtained were compared with standards of ICMR and WHO. Most of the parameters of the water from the Krishna River fall within the acceptable range set by the ICMR and WHO, according to the findings.